The Msi2 protein expression positive correlation with favorable cytogenetics findings in AML - Bakheet, Omayma Saad Eldeen; Nurasyikin Y,; Azma RZ,; Suria Abdul Aziz,; Chandramaya S,; Noraidah Masir, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2017)
Acute myeloid leukaemia (AML) is the most common subtype of acute leukaemias with a poor outcome. Msi2 protein is a newly discovered prognostic marker and it has been considered as a new target for therapy in AML. The study of Msi2 protein expression in AML cases has not been performed in Malaysia, to date. The main aim of the present study was to observe the expression of Msi2 protein in AML patients by immunohistochemistry (IHC) and to correlate its expression with the well-established prognostic and clinical parameters in AML as well as the overall survival (OS). Sixty four bone marrow trephine biopsy sections were immunostained for Msi2 protein. The percentage of blasts with positive reaction and the intensity of the cytoplasmic and nuclear staining were evaluated. The expression of Msi2 protein was found in 95.3% cases with Msi2 pattern varying between the cases. In 71.9% of cases, the blasts showed total cellular positivity and 23.4% cases showed only cytoplasmic positivity. Majority showed high expression of Msi2 for cytoplasmic staining. Interestingly, there was significant correlation between total cellular staining and the intermediate cytogenetic subgroup (P= 0.04). In conclusion, the results showed that the majority of the patients had high expression of Msi2 but this did not correlate to OS. However, the Msi2 expression correlated to the cytogenetic findings. The results suggest future extensive research to be conducted in order to ascertain the exact role of Msi2 positive blast cells in AML in our population and their association with prognosis and outcome.